Dynamic Brillouin cooling for continuous optomechanical systems. (1st March 2023) - Zhu, Changlong; Stiller, Birgit
Abstract: Up until now, ground state cooling using optomechanical interaction is realized in the regime where optical dissipation is higher than mechanical dissipation. Here, we demonstrate that optomechanical ground state cooling in a continuous optomechanical system is possible by using backward Brillouin scattering while mechanical dissipation exceeds optical dissipation which is the common case in optical waveguides. The cooling is achieved in an anti-Stokes backward Brillouin process by modulating the intensity of the optomechanical coupling via a pulsed pump to suppress heating processes in the strong coupling regime. With such dynamic modulation, a significant cooling factor can be achieved, which can be several orders of magnitude lower than for the steady-state case. This modulation scheme can also be applied to Brillouin cooling generated by forward intermodal Brillouin scattering.